2021
DOI: 10.3390/su132313345
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Hong Kong Youth Culture via a Virtual Reality Tour

Abstract: The advantages of employing virtual reality tours in teaching are attributed to the virtual reality experience it provides to the students. In the case of teaching popular culture, benefits from the potential of VR tour are amplified by the empirical significance that would lead to the students’ imagination and reflection. In addition, an online VR tour suggests a flexibility that allows students to learn anyplace anytime, satisfying the need for blended learning and distance learning, which is a very critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Significant technological advances are contributing to rethinking and elevating the instructional design so that educational materials that are more specifically applicable are provided to students at their appropriate level of learning. Moreover, the publications reviewed suggest that when using key technologies, learners feel inspired to learn, retain more knowledge, and are more interested in completing the assigned activities [65,66,70,143].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Significant technological advances are contributing to rethinking and elevating the instructional design so that educational materials that are more specifically applicable are provided to students at their appropriate level of learning. Moreover, the publications reviewed suggest that when using key technologies, learners feel inspired to learn, retain more knowledge, and are more interested in completing the assigned activities [65,66,70,143].…”
Section: Discussionmentioning
confidence: 99%
“…From a pedagogical and technological perspective, a thread emerges that co-design processes using XR and AI with more conventional resources still benefit learning [70,84]. With the advent of AI, new forms of online learning and teaching support appear to expand student satisfaction, knowledge acquisition, personalized programs [126], and intelligent tutoring-mentoring tools [91].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outbreak of COVID-19 has accelerated the large-scale implementation of online learning and mobile learning (Tang et al 2021 ), which have been found commonly applied in language teaching and learning (Cheung and Wang 2021 ; Wang 2023 ; Ying et al 2021 ). Various technologies are adopted to enhance online teaching and learning (e.g., ZOOM, Padlet, and Edpuzzle).…”
Section: Introductionmentioning
confidence: 99%